Casius Longinus’ Ars Rhetorica and the commentary to the Timaeus. Testimonies of Plato’s reception in Late Antiquity - Sánchez Castro, Liliana Carolina (Revista Archai, 2025)
The Ars Rhetorica of Cassius Longinus is not a work that has enjoyed particular popularity in studies of ancient rhetoricor on the philosophical activity in Late Antiquity. This is due, in part, to the shadow casted over this work by the anonymous treatise On Sublimity which was attributed to Cassius Longi-nus for a long time; in part, to the fact that this treatise and the rest of Cassius Longinus’ work is preserved in fragments; in part, because his most famous disciple, Porphyry, left his tute-lage to follow the teachings of the most reputed Plotinus, who considered Cassius Longinus a philologist, but not a philoso-pher. Regardless of the reasons that contributed to eclipse the work of Cassius Longinus, namely, the unphilosophical spirit Plotinus saw in him or the poor quality of the sources we have for his study; the work of this author carries valuable informa-tion for the reconstruction of intellectual activity of the time. My aim is to examine one of the cases where Cassius Longi-nus can be an exceptional witness of the scholarly and philo-sophical activity which constitutes the Platonic tradition in Late Antiquity. At the end of the Ars Rhetorica’s chapter devoted to utterance (περὶλέξεως) Cassius Longinus exposes his theory of rhetoric period. The fragments of the commentary that Cassius Longinus made on Plato’s Timaeus preserved in the commen-tary of Proclus sheds light on how Cassius Longinus received Plato’s dialogue and applied his exegetical work from a stylistic point of view (in accordance with his work in rhetoric), but also from a philological one. I want to explore, to the extent that the fragmentary material allows me, the link between logic and aesthetics emphasized in the Ars Rhetorica in the light of Cas-sius Longinus’ own exegetical work on Plato. Thus, it may be possible to reconcile the philological and philosophical work of our author while shedding light on one of the chapters of the Platonic tradition in Late Antiquity.